PENGIRIMAN BARANG DENGAN MENGGUNAKAN SEPEDA MOTOR - Deslida Saidah; Andri Andri (Institut Transportasi dan Logistik Trisakti, 2015)
In recent times, there is an increasing trend of logistics service companies. Every company has to perform well especially related to the on time delivery service if they want to bait many customers and compete in the logistics service industry. Otherwise, they will fall behind. Based on the research, there are five specific reasons of late delivery when the service is provided using motorcycles. They are the welfare factors, mentally and physically factors, the vehicle factors, the loading factors, and the IT tool factors. Using the qualitative and cause and effect method, the problems of late delivery can be solved. The solutions are training the couriers especially for time management and use of new technology, providing medical check up for couriers, motivating the couriers to give the best service to the clients, having some new motorcycles to back up the old ones, hiring new couriers and allocating time in routing them, and providing the best or at least good and reliable technology such as computers.